No gas source, no problem: Proximity to pre‐existing embolism and segmentation affect embolism spreading in angiosperm xylem by gas diffusion - Guan, Xinyi; Pereira, Luciano; McAdam, Scott A. M.; Cao, Kun‐Fang; Jansen, Steven (Plant, cell and environment, 2021)
Embolism spreading in dehydrating angiosperm xylem is driven by gas movement between embolized and sap‐filled conduits. Here we examine how the proximity to pre‐existing embolism and hydraulic segmentation affect embolism propagation. Based on the optical method, we compare xylem embolism resistance between detached leaves and leaves attached to branches, and between intact leaves and leaves with cut minor veins, for six species. Embolism resistance of detached leaves was significantly lower than that of leaves attached to stems, except for two species, with all vessels ending in their petioles. Cutting of minor veins showed limited embolism spreading in minor veins near the cuts prior to major veins. Moreover, despite strong agreement in the overall embolism resistance of detached leaves between the optical and pneumatic method, minor differences were observed during early stages of embolism formation. We conclude that embolism resistance may represent a relative trait due to an open‐xylem artefact, with embolism spreading possibly affected by the proximity and connectivity to pre‐existing embolism as a gas source, while hydraulic segmentation prevents such artefact. Since embolism formation may not rely on a certain pressure difference threshold between functional and embolized conduits, we speculate that embolism is facilitated by pressure‐driven gas diffusion across pit membranes. Application of the optical and pneumatic method shows that embolism spreading across xylem conduits may occur under different water potentials, depending on the proximity and interconduit connectivity to pre‐existing embolism. Hydraulic segmentation, however, may reduce this artefact considerably.